(untitled) (Journal on Excellence in College Teaching, 2024)
The similarities in outcomes of and intellectual development in faculty learning communities and student learning communities should encourage academic and student affairs colleagues to connect these two potentially successful approaches at their institutions. Yet in past years this linkage was not often made, missing an opportunity to create effective partnerships. The author examines the similarities of the two types of communities, describes attempts to achieve these connections, and provides recommendations for practice.